Perbandingan Pemeriksaan Jackson Cross Cylinder dan Fogging Clock Dial pada Penderita Astigmatisme di RS Mata Makassar - Siti Nur Auliana; Soraya Arifin; Eka Sari Ridwan; Purnamanita Syawal (RS Mata Makassar: Journal of Ophthalmology, 2025)
Astigmatism is a refractive error caused by differences in the curvature of the cornea or lens, resulting in light rays not being focused on a single point on the retina. Subjective examinations of astigmatism can be performed using the Jackson Cross Cylinder (JCC) technique and the Fogging Clock Dial method. This study aimed to compare the results of JCC and Fogging Clock Dial examinations in patients with astigmatism at Makassar Eye Hospital in 2025. The research used a descriptive quantitative design with a cross-sectional approach. The study sample consisted of 61 astigmatic patients obtained through accidental sampling. Examinations were conducted using JCC and Fogging Clock Dial to assess cylinder power and axis, and the results were compared using the Wilcoxon Signed-Rank Test. The findings showed that most respondents had low astigmatism, namely 75.4% in the right eye (OD) and 78.7% in the left eye (OS). The most frequent axis distribution was against the rule (ATR), both in JCC and Fogging Clock Dial examinations, with 50.8% in OD and 57.4% in OS. The Wilcoxon test obtained a p-value of 1.000, indicating no significant difference between JCC and Fogging Clock Dial in determining cylinder power and axis. Both JCC and Fogging Clock Dial examinations provided the same results in evaluating astigmatism power and axis. Thus, both methods can be effectively used in clinical practice for astigmatism patients.